A new species of Maxillaria (Maxillariinae) from the northern Andes and a new synonym of Maxillaria floribunda - Pisso-Florez, Gustavo Adolfo; Moreno, Juan Sebastián; Harding, Patricia A.; Baquero, Luis E. (Lankesteriana: International Journal on Orchidology, 2024)
Maxillaria andina, a new orchid species from high-Andean ecosystems of southwestern Colombia and northern Ecuador, is described. The new species is distinguished by having long and narrowly linear white sepals and petals with revolute margins, lip with mucronate epichile, and callus without hairs or trichomes. Distinguishing characters are provided to differentiate it from morphologically similar species, along with ecological and taxonomical notes. Additionally, Maxillaria sibundoyensis is synonymized with Maxillaria floribunda.